Proposals to clarify and enhance the naming of fungi under the International Code of Nomenclature for algae, fungi, and plants - Hawksworth, David L. (IMA Fungus, 2015)
Twenty-three proposals to modify the International Code of Nomenclature for algae, fungi, and plants adopted in 2011 with respect to the provisions for fungi are made, in accordance with the wishes of mycologists expressed at the 10(th) International Mycological Congress in Bangkok in 2014, and with the support of the International Commission on the Taxonomy of Fungi (ICTF), the votes of which are presented here. The proposals relate to: conditions for epitypification, registration of later typifications, protected lists of names, removal of exemptions for lichen-forming fungi, provision of a diagnosis when describing a new taxon, citation of sanctioned names, avoiding homonyms in other kingdoms, ending preference for sexually typified names, and treatment of conspecific names with the same epithet. These proposals are also being published in Taxon, will be considered by the Nomenclature Committee for Fungi and General Committee on Nomenclature, and voted on at the 19(th) International Botanical Congress in Shenzhen, China, in 2017.